If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 34 + -5(p + 1) = 4 Reorder the terms: 34 + -5(1 + p) = 4 34 + (1 * -5 + p * -5) = 4 34 + (-5 + -5p) = 4 Combine like terms: 34 + -5 = 29 29 + -5p = 4 Solving 29 + -5p = 4 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-29' to each side of the equation. 29 + -29 + -5p = 4 + -29 Combine like terms: 29 + -29 = 0 0 + -5p = 4 + -29 -5p = 4 + -29 Combine like terms: 4 + -29 = -25 -5p = -25 Divide each side by '-5'. p = 5 Simplifying p = 5
| -4(x-2)=9 | | -4(x-2)=9 | | 3(n-5)=-21 | | 3x/4-36/4-3x/38-8/38=3x/11+4/11+16/36+2x/36 | | 4(5x+2)=28 | | 6x/3-2(x-4)/3=8 | | (10x+9y)+(14x)+(6y)=180 | | 9/5x=16 | | 18m^2+8n^2-24mn-6m+4n=0 | | 4/5x=16-x | | 3m=m+16 | | (36x^2+45x+8)/9 | | (log^2x^2)-2logx-3=0 | | 6y-12y= | | -0.04w=-0.96 | | 120/x=16 | | 1.5d=0.5625 | | -2.2=c-(-0.8) | | -0.6=0.3t | | 6x-2(x-4)=8/3 | | -0.4s=0.48 | | 6y^2-17y+12=0 | | 4a-12=3a+12a | | x^2-49=9 | | x^2-49=9 | | 1/5((5/2)/(1/12)) | | 12(2/3)^3 | | h=12(2/3)^3 | | 6x+7=64-2x | | 6x+7=63-3x | | 6x+38=13x-17 | | -2+-3u=0 |